2021
DOI: 10.1007/s40843-021-1711-5
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-order phase transitions in RE6Co2Ga (RE = Ho, Dy or Gd) cryogenic magnetocaloric materials

Abstract: Rare-earth (RE) rich intermetallics crystallizing in orthorhombic Ho6Co2Ga-type crystal structure exhibit peculiar magnetic properties that are not widely reported for their magnetic ordering, order of magnetic phase transition, and related magnetocaloric behavior. By tuning the type of RE element in RE6Co2Ga (RE = Ho, Dy or Gd) compounds, metamagnetic anti-to-paramagnetic (AF to PM) phase transitions could be tuned to ferro-to-paramagnetic (FM to PM) phase transitions. Furthermore, the FM ground state for Gd6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…It has been theoreticaly justified and experimentaly evidenced in the series of compound families 32 that overshooting of n = 2 value is one of the hallmarks unequivocally corresponding to the first order magneto-structural phase transitiuon (FOPT). Employing the criterion, FOPT has been recognized in RE 6 Co 2 Ga compounds when RE = Ho, Dy, wherease only SOPT has been observed in the case of introducing Gd 33 . Accurate determination of the phase transition nature is important both from fundamental and application point of view.…”
Section: Discussionmentioning
confidence: 99%
“…It has been theoreticaly justified and experimentaly evidenced in the series of compound families 32 that overshooting of n = 2 value is one of the hallmarks unequivocally corresponding to the first order magneto-structural phase transitiuon (FOPT). Employing the criterion, FOPT has been recognized in RE 6 Co 2 Ga compounds when RE = Ho, Dy, wherease only SOPT has been observed in the case of introducing Gd 33 . Accurate determination of the phase transition nature is important both from fundamental and application point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The order of MPT can be checked by the novel MC criterion proposed by Law et al [24,53,54], i.e., based on the field dependence exponent n of the ΔS M (T) curves, which can be estimated using the following formula:…”
Section: T T T T T T T T T T T T = (mentioning
confidence: 99%
“…Xu et al [20] recently reported an MC effect in ferromagnetic Sr 2 GdNbO 6 double-perovskite oxide with the −ΔS M max value of 29.7 J kg −1 K −1 under ΔH of 0-7 T at around 2 K. In recent years, we have fabricated several series of RE-based materials and checked their magnetic properties, MPT, and MC effects in detail; several of these materials exhibited promising MC performances. For instance, large MC effects in a wide temperature range from the liquefaction temperature of H 2 to N 2 have been noted in RE 6 Co 2 Ga compounds [24]. A table-like MC effect has been achieved in the highentropy Er 20 Ho 20 Gd 20 Ni 20 Co 20 amorphous alloys [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations